Insect Herbivory-Elicited GABA Accumulation in Plants is a Wound-Induced, Direct, Systemic, and Jasmonate-Independent Defense Response - Scholz, Sandra S.; Reichelt, Michael; Mekonnen, Dereje W.; Ludewig, Frank; Mithöfer, Axel (Frontiers in Plant Science, 2015)
The non-proteinogenic amino acid γ-aminobutyric acid (GABA) is present in all organisms analyzed so far. In invertebrates GABA acts as a neurotransmitter; in plants different functions are under discussion. Among others, its involvement in abiotic stress reactions and as a defensive compound against feeding insects is suggested. GABA is synthesized from glutamate by glutamate decarboxylases and degraded by GABA-transaminases. Here, in Arabidopsis thaliana, gad1/2 double mutants showing reduced GABA concentrations as well as GABA-enriched triple mutants (gad1/2 x pop2-5) were generated and employed for a systematic study of GABA induction, accumulation and related effects in Arabidopsis leaves upon herbivory. The results demonstrate that GABA accumulation is stimulated by insect feeding-like wounding by a robotic caterpillar, MecWorm, as well as by real insect (Spodoptera littoralis) herbivory. Higher GABA levels in both plant tissue and artificial dietary supplements in turn affect the performance of feeding larvae. GABA enrichment occurs not only in the challenged but also in adjacent leaf. This induced response is neither dependent on herbivore defense-related phytohormones, jasmonates, nor is jasmonate induction dependent on the presence of GABA. Thus, in Arabidopsis the rapid accumulation of GABA very likely represents a general, direct and systemic defense reaction against insect herbivores.